Determination of the Central Axis of the Scaphoid - Heaton, Dennis J.; Trumble, Thomas; Rhodes, Diana (Journal of Wrist Surgery, 2015)
Purpose Determine the central axis of the scaphoid and its relation to surrounding anatomic landmarks to facilitate internal fixation of the scaphoid.Methods Seventeen cadaveric dissections of the wrist were performed. Measurements of the height and width of the proximal pole, waist, and distal pole were made. The midpoint of the height and width of each measurement were plotted on a scatter plot graph and a forecast line was developed. The formula of the resultant line was used to calculate the position of the central axis at the proximal pole, waist, and distal pole. The inverse tangent of the slope of the line was then used to determine the angle of the line from proximal to distal.Results The average central axis fell along a line measuring at points from the ulnar to the radial border and from the dorsal to the volar border of the proximal pole, waist, and distal pole at 7.86 mm, 7.61 mm, and 7.31 mm respectively; an angle of 13.78 degrees from ulnar to radial and dorsal to volar. The proximal point can be determined by measuring ∼44 mm radially from the ulnar styloid along the watershed line of the radius and 14 mm volar from the dorsal tip of the Lister tubercle. The distal point can be determined by measuring ∼4 mm ulnar from a line extending distally from the volar radial corner, and 7 mm volar from the most dorsal point of the combined surface of the trapezium and triquetrum. No significant difference existed between male and female specimens.Conclusions The central axis of the scaphoid can be described to exist along a line extending from the relative central point of the proximal pole, measured 7.86 mm radial from the scapholunate ligament and 8.31 mm volar of the most dorsal point; through the waist, and extending to the relative central point of the distal pole measured 3.77 mm ulnar of the volar radial corner and 7.36 mm volar of the most dorsal point at an angle directed radially and volarly at 13.78 degrees.Level of Evidence Level IIIType of Study Diagnostic/ therapeutic.
Keywords: scaphoid axis; scaphoid anatomy; scaphoid targeting; volar scaphoid approach